Clinical practice guideline for the management of hypertension in China - Chinese Society of Cardiology, Chinese Medical Association; Hypertension Committee of Cross-Straits Medicine Exchange Association; Cardiovascular Disease Prevention and Rehabilitation Committee, Chinese Association of Rehabilitation Medicine; Rongman Jia (Chinese Medical Journal, 2024)
Abstract. In China, hypertension is the most common chronic non-communicable disease and the most significant risk factor for cardiovascular mortality among urban and rural residents. To standardize the clinical diagnosis and treatment of hypertension and to improve the prevention and control level of hypertension in China, Chinese Society of Cardiology, Chinese Medical Association; Hypertension Committee of Cross-Straits Medicine Exchange Association; Cardiovascular Disease Prevention and Rehabilitation Committee, Chinese Association of Rehabilitation Medicine, jointly collaborated to formulate the Clinical Practice Guideline for Hypertension Management in China. The Grading of Recommendation, Assessment, Development, and Evaluation (GRADE) approach was used to rate the quality of evidence and strength of recommendations, and the reporting items for practice guidelines in healthcare (RIGHT) were followed to establish the guideline. Detailed evidence-based recommendations for the diagnosis, evaluation, and treatment of 44 clinical questions in the field of hypertension, including essential and secondary hypertension, have been provided to guide clinical practice. Registration:. International Practice Guidelines Registry Platform, http://www.guidelines-registry.cn/, No. IPGRP-2021CN346.